The Legal Aspect of Fingering Mother Cap in the Making of Land & Buying Deals - Anik Setiawan (Sultan Agung Notary Law Review, 2021)
The research objective is to unto know and analyze application Affixing the thumbprint in making land sale and purchase deeds, unto know and analyze legal consequences of affixing a thumbprint in the making of a land sale and purchase deed, and untuk know and analyze the extent of the function Affixing the thumb print in the making of the land sale and purchase deed. This research is a qualitative research with a normative juridical approach.This research was conducted in Kendal Regency. Based on the results of research and discussion it can be seen that " The application of the thumbprint affixing in making the sale and purchase deed of the tappers in minuta by the notary / PPAT is to identify the presence of the tappers. Proof of presence that the person who comes to the Notary / PPAT is the person concerned who wants to make a Notary / PPAT Deed, not someone else. The thumbprint affixing has legal consequences in the making of the Land Sale and Purchase Deed because it has benefits before the signing of the deed by the notary so that the notary still has the opportunity to correct previously unseen mistakes. One of the purposes of affixing the thumbprint before signing the deed is that It is a guarantee for the parties that the signed deed is the same as what has been read, and the deed is read so that the parties can be certain that the writing or content of the deed is true to the wishes of the tappers. The function in the application of affixing a thumbprint in making deeds is to identify the presence of tappers. Proof of presence that the person who came to the Notary / PPAT was the person concerned who wanted to make a Notary / PPAT Deed, not someone else. The obligation to attach the tappers' fingerprints to the Minuta Deed of Notary / PPAT aims to anticipate if one day the tappers deny their signature on the Minuta Deed of Notary / PPAT, then as additional evidence used the tapping's fingerprint. Suggestions were submitted for compliance and legal awareness from the community Affixing the thumbprint in the making of the land sale and purchase deedIt must be improved, among others, through legal counseling, distribution of pamphlets related to land law issues in a communicative language so that it can be understood by the general public, or through other reading materials, and also through the mass media so that through various methods it is expected people who were previously blind to the law can know and understand the law. And if you already know and understand the law, then this will be able to increase the degree of compliance and legal awareness of the community in the field of land law.